2020
DOI: 10.3390/molecules25061270
|View full text |Cite
|
Sign up to set email alerts
|

BEL β-Trefoil Reduces the Migration Ability of RUNX2 Expressing Melanoma Cells in Xenotransplanted Zebrafish

Abstract: RUNX2, a master osteogenic transcript ion factor, is overexpressed in several cancer cells; in melanoma it promotes cells migration and invasion as well as neoangiogenesis. The annual mortality rates related to metastatic melanoma are high and novel agents are needed to improve melanoma patients’ survival. It has been shown that lectins specifically target malignant cells since they present the Thomsen–Friedenreich antigen. This disaccharide is hidden in normal cells, while it allows selective lectins binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Different lectins with b-trefoil folding were reported to have antitumor effects both in cell lines (Bovi et al, 2013) and in a melanoma xenografted zebrafish model (Valenti et al, 2020) and to induce apoptosis with the activation of MAPK and stressactivate kinase pathways in addition to NF-kB (Hasan et al, 2019). Moreover, it was previously shown that TNF-a-mediated signaling pathway and apoptosis can be elicited in hematological cells by several lectins upon binding to surface receptors, like globotriaosylceramide (Gb3) carbohydrate chain (Hosono et al, 2014;Liao et al, 2016;Chernikov et al, 2017), which is also a known receptor for Shiga toxins (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Different lectins with b-trefoil folding were reported to have antitumor effects both in cell lines (Bovi et al, 2013) and in a melanoma xenografted zebrafish model (Valenti et al, 2020) and to induce apoptosis with the activation of MAPK and stressactivate kinase pathways in addition to NF-kB (Hasan et al, 2019). Moreover, it was previously shown that TNF-a-mediated signaling pathway and apoptosis can be elicited in hematological cells by several lectins upon binding to surface receptors, like globotriaosylceramide (Gb3) carbohydrate chain (Hosono et al, 2014;Liao et al, 2016;Chernikov et al, 2017), which is also a known receptor for Shiga toxins (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As in mammals, three stages can be recognized in the osteogenic differentiation: an early stage characterized by runx2a and runx2b expression; an intermediate stage characterized by osterix gene expression; and a maturation stage characterized by the expression of osteocalcin, osteonectin, collagens, and other bone matrix genes ( Li et al, 2009 ; Knopf et al, 2011 ). Zebrafish has been proposed as a useful in vivo model for studying cell signaling in bone ( Valenti et al, 2020a ) and for evaluating the effects of bone treatments ( Valenti et al, 2020b ). Zebrafish are frequently used in developmental biology ( Suniaga et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other tested compounds using zebrafish models were recently demonstrated to possess antimelanoma potential. Among them are diphlorethohydroxycarmalol [286], theaflavin [287], ellagic acid [288], inularin [289], and BEL β-trefoil [290].…”
Section: Zebrafish Modelmentioning
confidence: 99%